Calculation of wood reinforced concrete girder bridge - Yuriy Vladimirovich Nemirovsky; Artem Ivanovich Boltaev (Вестник СибАДИ, 2017)
This paper presents a general approach to the calculation of beam spans wood concrete bridge by taking into account physical nonlinearity and different resistance materials as well as the actual loading conditions. In general, it is assumed that a part of the concrete, and the wooden part represent a layered substructure made of different types of concrete and wood. A method for solving systems of nonlinear equations resolution, which has significant advantages in comparison with the iterative methods. Examples of calculations showing the possibility of a significant increase, both strength and rigidity of the structure due to a combination of different types of wood in the cross section. The important feature of the layered construction work under load, namely the possibility of latent forms of destruction when the initial breakdown occurs in the inner layers of the cross-section.